Peran Pendidikan Anak Usia Dini pada Perubahan Sosial Masyarakat di Dusun Cicurug Desa Cibanten - Ia Rahmawati; Iip Apipah; Lisa Noviyani (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2024)
This research aims to describe the role of early childhood education in social change in the community in Cicurug Hamlet, Cibanten Village. The method used is a qualitative method with a case study approach. The data collection process uses the results of observations, interviews and documentation. The results of the research show that in Cibanten Village early childhood education has a role in social change in society. Supported by the emergence of various types of PAUD ranging from (TK, RA, and KOBER) in the area. From various sources obtained and studied, it results in an understanding that education is a very important thing in life. The important role of education in life and social change is to equip and prepare children to face or overcome various problems that will occur as a result of social change. So the efforts made in Cibanten Village are currently that children aged three to six years are required to enter early childhood education before entering the next level of education. Providing education is important for people's lives to impact change towards progress.